2015
DOI: 10.1002/anie.201504665
|View full text |Cite
|
Sign up to set email alerts
|

18F‐Labeling of Aryl‐SCF3, ‐OCF3 and ‐OCHF2 with [18F]Fluoride

Abstract: We report that halogenophilic silver(I) triflate permits halogen exchange (halex) nucleophilic (18)F-fluorination of aryl-OCHFCl, -OCF2Br and -SCF2Br precursors under mild conditions. This Ag(I)-mediated process allows for the first time access to a range of (18)F-labeled aryl-OCHF2, -OCF3 and -SCF3 derivatives, inclusive of [(18)F]riluzole. The (18)F-labeling of these medicinally important motifs expands the radiochemical space available for PET applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
72
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 88 publications
2
72
0
2
Order By: Relevance
“…We were naturally eager to extend the methodology to other fluoroalkylsulfonyl chlorides as radical precursors for the synthesis of the potentially useful chiral β-difluoromethyl or difluoroacetyl amines. To our delight, the reaction of N -alkenyl urea substrate 1a with 2b under the otherwise identical reaction conditions delivered difluoroacetyl-containing product 4A in 97% yield with 85% ee, which containing an acetyl structure is especially appealing because further transformations of the acetyl group in the obtained product would give access to a more diverse class of structures5960. Further improvement of the stereoselectivity indicated that lowering the reaction temperature was obviously beneficial for such a process, giving 4A in 95% yield with 97% ee at 0 °C (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…We were naturally eager to extend the methodology to other fluoroalkylsulfonyl chlorides as radical precursors for the synthesis of the potentially useful chiral β-difluoromethyl or difluoroacetyl amines. To our delight, the reaction of N -alkenyl urea substrate 1a with 2b under the otherwise identical reaction conditions delivered difluoroacetyl-containing product 4A in 97% yield with 85% ee, which containing an acetyl structure is especially appealing because further transformations of the acetyl group in the obtained product would give access to a more diverse class of structures5960. Further improvement of the stereoselectivity indicated that lowering the reaction temperature was obviously beneficial for such a process, giving 4A in 95% yield with 97% ee at 0 °C (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The specific activity of the quinoline 2 s was determined to be about 21 mCi mmol À1 at the end of synthesis (see the Supporting Information for details), which is comparable with the recently reported arylÀ [ 18 F]CF 3 [5a] and arylÀ[ 18 F]SCF 3 labeling. [15] In summary, we have successfully developed an efficient, fast, and transition-metal-free trifluoromethylthiolation method with a wide substrate scope and applicability. This strategy has been successfully applied to [ 18 F]trifluoromethylthiolation of alkyl electrophiles, and is the first example of [ 18 F]CF 3 S labeling.…”
Section: Methodsmentioning
confidence: 99%
“…[2] As ac onsequence,c onsiderable efforts have been devoted to the development of efficient methods for the preparation of 18 Flabeled PET radiotracers. [3] Them ajority of 18 F-labeling methods reported to date have focused on the direct [ 18 F]fluorination of pre-functionalized arenes and alkanes, [4] while radiosynthetic routes towards 18 F-labeled molecules with functional groups such as [ 18 F]CF 3 , [5] [ 18 F]CF 2 H, [6] [ 18 F]SCF 3 , [7,8] [ 18 F]OCF 2 H, [8b] and [ 18 F]OCF 3 [8b] have appeared only more recently.Within this series,the trifluoromethylthiol group (-SCF 3 )h as gained much attention in the context of medicinal chemistry,d ue to its beneficial effects on pharmacokinetic and physicochemical properties,i ncluding metabolic stability and lipophilicity. [9] In 2015, Gouverneur and co-workers reported the first radiosynthetic route towards [ 18 F]arylSCF 3 via halogen exchange (halex) of ArSCF 2 Br with cyclotron-produced 18 Ffluoride ( Figure 1A).…”
mentioning
confidence: 99%